Cannabinoid Receptor 2 Agonist JWH-015 Inhibits Interleukin-1β-Induced Inflammation in Rheumatoid Arthritis Synovial Fibroblasts and in Adjuvant Induced Arthritis Rat via Glucocorticoid Receptor - Fechtner, Sabrina; Singh, Anil K.; Srivastava, Ila; Szlenk, Christopher T.; Muench, Tim R.; Natesan, Senthil; Ahmed, Salahuddin (Frontiers in Immunology, 2019)
Management of pain in the treatment of rheumatoid arthritis (RA) is a priority that is not fully addressed by the conventional therapies. In the present study, we evaluated the efficacy of cannabinoid receptor 2 (CB2) agonist JWH-015 using RA synovial fibroblasts (RASFs) obtained from patients diagnosed with RA and in a rat adjuvant-induced arthritis (AIA) model of RA. Pretreatment of human RASFs with JWH-015 (10-20 µM) markedly inhibited the ability of pro-inflammatory cytokine interleukin-1β (IL-1β) to induce production of IL-6 and IL-8 and cellular expression of inflammatory cyclooxygenase-2 (COX-2). JWH-015 was effective in reducing IL-1β-induced phosphorylation of TAK1 (Thr184/187) and JNK/SAPK in human RASFs. While the knockdown of CB2 in RASFs using siRNA method reduced IL-1β-induced inflammation, JWH-015 was still effective in eliciting its anti-inflammatory effects despite the absence of CB2, suggesting the role of non-canonical or an off-target receptor. Computational studies using molecular docking simulations showed that JWH-015 favorably binds to glucocorticoid receptor (GR) with the binding affinity and kinetics similar to its ligand dexamethasone. Furthermore, knockdown of GR using siRNA abrogated JWH-015’s ability to reduce IL-1β-induced IL-6 and IL-8 production. In vivo, administration of JWH-015 (5 mg/kg, daily i.p. for 7 days at the onset of arthritis) significantly ameliorated AIA in rats. Pain assessment studies using von Frey method showed a marked antinociception in AIA rats treated with JWH-015. In addition, JWH-015 treatment inhibited bone destruction as evident from micro-CT scanning and bone analysis on the harvested joints and modulated serum RANKL and OPG levels. Overall, our findings suggest that CB2 agonist JWH-015 elicits anti-inflammatory effects partly through GR. This compound could further be tested as an adjunct therapy for the management of pain and tissue destruction as a non-opioid option for RA.